Effect of crack position and loading conditions on SIF in SiC particles reinforced Al composite - Aicha Metehri; Madani Kouider; Abdelkader Lousdad (Fracture and Structural Integrity)
In this paper the effect of reinforcement crack position and loading conditions (in mode I) on the stress intensity factors of the Al/SiCp metal matrix composite was examined using a finite element method. A simple cubic cell model with square reinforcement shapes was developed to investigate its effect on the mechanical properties of the MMC. The finite element technique was used to calculate the stress intensity factors KI and KII for crack in the matrix and in particle. The particle and matrix materials were modelled in linear elastic conditions. The obtained results show the important role on the stress intensity factors played by the relative elastic properties of the particle and matrix. The results also show that the loading conditions and inter-distance between two particles with two interfacial cracks has an important effect on the KI and KII stress intensity factors.